Impactos da estrutura ocupacional na distribuição dos rendimentos de 2002 a 2014: um comparativo entre o Brasil e o nordeste - Santos, Patrick Leite (2017)
The unequal distribution of income from production is one of the chronic problems of modern society and one of the hindrances to the development and social and economic growth, especially of underdeveloped countries at the potential level. Brazil has a high level of inequality, with a more acute incidence in the Northeast region. Given this, the objective of this dissertation is to analyze the impacts of the occupational structure on income distribution from 2002 to 2014, comparing Brazil and the Northeast macro-region. For that, the Gini income distribution, Theil's T and concentration ratio, and ordinary least squares (OLS), quantile regression (RQ) and interquartile regression (IR) are used as the methodology. The microdata used were extracted from the Pesquisa Nacional por Amostra de Domicílios (PNAD) database, made available by the Instituto Brasileiro de Geografia e Estatística (IBGE). The results obtained, interpreted in the light of the theory of personal income distribution, show evidence that the income distribution within the occupational structure improved from 2002 to 2014 in a generalized way in the three dimensions of the occupational structure (branches of activity, position in occupation and occupation) in the two geographical cuts. It has been found that the improvement of distribution has occurred in parallel with the improvement of levels of education and income and the increase in the participation of women and non-whites. The MQO and RQ results show that some of the traditional sectors, such as agriculture and livestock, which have a large relative participation, have a lower monetary return than other sectors, even with a reduction in the difference between 2002 and 2014, which negatively impacts income distribution. As confirmed by RI, which points to this sector as the most unequal. It is also revealed that the increase in the formalization of the labor force has a greater impact in the Northeast, where the difference in the monetary return in relation to the employee without a formal contract, measured by the MQO and RQ, is greater. In addition, IR shows that the inequality of remuneration among employees with a portfolio is lower in the Northeast. Finally, it is observed that the occupations of agricultural workers and workers in services and commerce, have the lowest monetary returns, for the average and all quantiles, besides a high level of concentration, behind only occupations of manager, professionals science and arts, and middle-level technicians, respectively, which negatively impacts the distribution of income, especially in the Northeast, where these occupations have a high participation.